Pengaruh Perbedaan Jumlah Dan Posisi Saluran Masuk (Ingate) Terhadap Hasil Coran Produk Connecting Rod Dari Bahan Aluminium - OKTAFIAN SETYO NUGROHO, OKI, PATNA PARTONO, ST, MT (2016)
This study aims to determine the effect of differences in the number and position of the inlet to the shrinkage, defects porosity, hardness and micro photograph. The raw material of this study is aluminum used or rosok of various components of the re-casted. This research examined the number and position of the inlet one, two, and three. Testing will be done antaralain chemical composition test, test shrinkage, density test, Brinell hardness test (ASTM standard E 10), and a micro photograph test (ASTM standard E 3). The results showed that the results of chemical composition found chemical elements (Al) 91.60%, silicon (Si) 2:51%. So from the elements present this material include metal aluminum silicon alloy (Al-Si). The average yield is highest shrinkage in the location of the inlet (ingate) one at 2.52%, while the inlet (ingate) two 1.82%, and the inlet (ingate) 2.08% The results of the three highest density found in (ingate) two amounted to 2.38, while the (ingate) of 2.35, and (ingate) three 2.36. Prices are at the highest hardness (ingate) two 70.34 (HBN), whereas (ingate) a 69.04 (HBN), and (ingate) three 69.81 (HBN).